Stress evolution and strain partitioning along the active western Pangea margin during its breakup. Petrochronology and microtectonics of the Otu- Pericos Shear Zone, Northern Andes, Colombia - Morales Galeano, Alejandro (2025)
Major episodes of plate reorganization and continental mass distribution represent fundamental processes in Earth Sciences, imposing first-order boundary conditions on the evolution of orogenic systems and Earths surface environment. Along the Northen Andes, the Otu-Pericos Shear Zone (OPSZ) preserves a long-lived record of lithospheric deformation and metamorphism associated with plate-kinematic reorganizations resulting from the breakup of western Pangea. This study integrates field-based structural mapping, microstructural and petrochronological analyses, and thermodynamic modeling to reconstruct the deformation history and stress evolution recorded along the OPSZ. Field and structural observations reveal the juxtaposition of several tectonic blocks characterized by contrasting strain geometries, metamorphic grades, and deformation intensities. The nature of the block contacts indicates that these boundaries acted both as strain localization zones and as hydrothermal fluid conduits. Within single deformation episodes, strain partitioning occurred as spatial gradients, with high-strain fabrics concentrated in the shear zone core, and as three-dimensional variations in strain geometry within individual lithological units, which preserve both foliated and blocky structures. The reactivation of pre-existing anisotropies promoted the establishment of new shear loci, emphasizing the role of inherited structures in localizing deformation and guiding the progressive growth of the shear zone. Microtectonic characterization combined with in-situ multi-mineral petrochronology (Lu-Hf in Garnet, U-Pb-REE in titanite and apatite, and Rb-Sr in mica) establishes direct temporal and physical relationships between deformation and metamorphism. Garnet constrains the timing of high-pressure metamorphism associated with tectonic burial and accretion. Titanite records both metamorphic growth and isotopic resetting of its igneous precursor, while apatite captures cooling and isotopic resetting during greenschist-facies exhumation. Muscovite ages reflect multiple processes, including the formation and reactivation of tectonic fabrics under distinct stress regimes, hydrothermal alteration, and late-stage strike-slip reactivation. Integration of these datasets constrains four major shifts in the regional stress regime, linked to large-scale plate reorganizations associated with Pangeas breakup: (1) ~200 Ma, transition from extensional to transtensional regime during drift and early subduction initiation; (2) ~170 Ma, onset of transpression and accretion of trench-sediments; (3) ~112 Ma, renewed extension and exhumation driven by the arrival of a mid-ocean ridge and propagation of Atlantic spreading; and (4) ~65 Ma strike-slip reactivation associated with the onset of Andean accretionary tectonics. These results demonstrate that deformation along the OPSZ was a continuous yet partitioned processes, where evolving stress regimes produced complex overprinting patterns that may mimic polyphase deformation. The integrated microtectonic and petrochronological approach applied here provides a coherent framework for elucidating how plate-kinematic interactions govern the style, timing, and metamorphic overprint of the lithospheric deformation front during major plate reorganizations.